(untitled) (TEST Ticontre. Theory Text Translation, 2025)
The essay explores the relationship between identity, nostalgia, and cultural memory in Georgi Gospodinov’s Time Shelter. The analysis aims to reflect on how the novel portrays the dynamics and risks involved in reconfiguring the past within the context of contemporary European society. Combining literary theory and cultural memory studies, the paper examines two pivotal elements of the novel, namely the autofictional genre and “time shelters”—time rooms that allow individuals to experience the past as if immersing themselves in the fictional worlds of literature. Particular attention is given to the double, ambivalent nature of (auto)fictional writing as both a biased mediator of cultural memory and a genuine tool for constructing personal identity. L’articolo indaga il legame tra identità, nostalgia e memoria culturale in Cronorifugio di Georgi Gospodinov. L’obiettivo dell’analisi è esaminare i modi in cui il romanzo rappresenta le dinamiche e i rischi connessi alla riemersione nostalgica del passato nel contesto della società europea contemporanea. Affiancando gli strumenti e le tesi dei cultural memory studies ai ferri del mestiere della teoria letteraria, il saggio si focalizza su due importanti componenti romanzesche: il carattere autofinzionale della scrittura e i “cronorifugi”, stanze del tempo che permettono di fare esperienza del passato secondo modalità simili all’immersione nei mondi della finzione letteraria. Particolare attenzione è posta alla funzione bifida della scrittura (auto)finzionale, mediatrice tendenziosa della memoria culturale e allo stesso tempo strumento autentico di costruzione dell’identità personale.